Implementasi Metode Talqin dalam Menghafal Al-Qur’an di Sekolah Dasar Negeri 19 Luhak Nan Duo Kabupaten Pasaman Barat - Azzuhra, Ulfa; Ikhlas, Al (ALSYS, 2023)
The talqin method is a method of memorizing the Koran by the teacher exemplifying verses or dictating verses to students, the students repeat what the teacher exemplifies. Of the 51 grade 3 students, most of them could not read the Koran, the average student was still at the iqra reading stage, therefore the teacher applied the talqin method to make it easier for students to memorize the Koran. This study aims to determine the implementation of the talqin method in memorizing the Koran at SD Negeri 19 Luhak Nan Duo, West Pasaman Regency, its supporting and inhibiting factors, as well as the form of evaluation of the talqin method in memorizing the Koran. This research includes qualitative research with a descriptive approach. the data analysis techniques used are data collection, data reduction, data presentation, and data verification. The results showed that the implementation of the talqin method in memorizing the Koran at 19 Luhak Nan Duo Elementary School, West Pasaman Regency, went through three stages, namely planning, implementation, and evaluation. First, the planning for the talqin method has been made by the school which includes a schedule of tahfidz activities for each class and the tahfidz supervising teacher makes a postcard, a list of attendees. And the assessment criteria are makhrijul letters, fluency, and tajwid. The supporting factors for the application of the talqin method are motivation from teachers, parents, friends, and using murattal.